2000
DOI: 10.1094/pdis.2000.84.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilization on Disease Progress of Rice Blast on Susceptible and Resistant Cultivars

Abstract: The effects of three nitrogen fertilization treatments on the development of rice blast were studied on eight cultivars under field conditions in Arkansas in 1995 and 1996. The eight cultivars (Kaybonnet, Cypress, Lacassine, Mars, Adair, Alan, Newbonnet, and RT7015) ranged from resistant to susceptible to blast according to previous field observations. The recommended nitrogen levels for the eight cultivars varied from 123 to 168 kg/ha/year. Three treatments, consisting of different rates and timing of nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
2
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 11 publications
8
71
2
7
Order By: Relevance
“…Agricultural practices that lead to significant discrepancies in nitrogen availability (in terms of quantity, form and balance with other nutrients) are likely to result in variations in the incidence of diseases such as rice blast (Primavesi et al 1972;Séguy et al 1981Séguy et al , 1989Long et al 2000;Walters and Bingham 2007). High concentrations of these compounds in plant cells also make them more attractive to certain pests, particularly sucking insects (Chaboussou 2004;Jahn et al 2005;Lu et al 2007).…”
Section: Non-preference (Antixenosis)-like Resistancementioning
confidence: 99%
“…Agricultural practices that lead to significant discrepancies in nitrogen availability (in terms of quantity, form and balance with other nutrients) are likely to result in variations in the incidence of diseases such as rice blast (Primavesi et al 1972;Séguy et al 1981Séguy et al , 1989Long et al 2000;Walters and Bingham 2007). High concentrations of these compounds in plant cells also make them more attractive to certain pests, particularly sucking insects (Chaboussou 2004;Jahn et al 2005;Lu et al 2007).…”
Section: Non-preference (Antixenosis)-like Resistancementioning
confidence: 99%
“…Rice blast (Kürschner et al 1992;Long et al 2000) is the best-known example of such a disease. Among wheat diseases, powdery mildew (Last 1953;Teich et al 1987), leaf rust (Howard et al 1994;Teich et al 1987), stripe rust or yellow rust (Ash and Brown 1991;Danial and Parlevliet 1995) and several other diseases (Howard et al 1994) have been reported to increase in severity as the rate of nitrogen application is increased.…”
Section: Effect Of Abiotic Stress On Carbohydrate Content and Resistamentioning
confidence: 99%
“…Disease management is based mainly on efficient use of nitrogen fertilization (Webster and Gunnell 1992;Long et al 2000), use of resistant cultivars, crop rotation, maintaining a proper flood level and treatment with fungicides (TeBeest et al 2007;Maciel 2011). Surveys conducted in 2009 showed that in Italy the 75 % of the rice area is treated against blast disease and the 94 % of treated surface is treated with tricyclazole, mainly by a single treatment (Di Tullio and Baldi 2011).…”
Section: Introductionmentioning
confidence: 99%